Web Channel for a Mobile money system - Pereira, Rúben Filipe Simões (2019)
Nowadays, 31% of the population worldwide still classified as Underbanked. These do not have access to mainstream financial services or institutions, and this is a problem that especially haunts the emerging markets. As the mobile phone penetration rate is tremendous, financial companies are investing in the development of mobile banking solutions to solve this issue. M-Pesa is one of those solutions that currently is being developed and deployed in several of these markets as in Tanzania, Mozambique, Democratic Republic of the Congo and others. The appearing of solutions like M-Pesa allowed its users to have an online bank account and perform operations as deposit, transfer or withdraw money. Despite the innovation and these solutions give them the possibility of pay taxes, bills or services, they continue excluded from the online shopping world. This exclusion happens because payment gateways are not prepared to support users that do not use the traditional banking systems. Online Payments platform aims to allow M-Pesa users to shop online. This platform is an online payment gateway that recurring to a third-party payment processor allows M-Pesa users to purchase on online stores. Is part of the prototype a web platform, that is composed by the following portals: i) merchant; ii) developer; iii) checkout; iv) documentation and v) demo and the Android M-Pesa application that was used to add support to new features for the Online Payments platform. This platform is a proof of concept developed during an internship at WIT Software, that is the company responsible for the development process of the M-Pesa mobile applications. Finally, as far as the final phase of the project is concerned, have been obtained proof of concept thought which can see that it is possible to implement it.